Development of Speed Training Equipment and Dollyo Chagi's Taekwondo Kick Speed Endurance Using Pyongyo - Alhumary, Farid M.; Swandana, Atika; Sirait, Wahyu Alexandrian; Simangunsong, Yessy Veronika (INSPIREE: Indonesian Sport Innovation Review, 2024)
The  purpose  of  the study. The context of this research is that coaches and trainers must be able to adapt to competition as a result of the continuously changing technological landscape in the coaching process . Staying focused throughout training is the trainer's responsibility. This is important because, in addition to monitoring training progress, the trainer's role during sessions also requires the ability to evaluate programme results. To train the speed and endurance of kicks for taekwondo players , this research aims to design a speed and endurance training tool for Dollyo kicks. Chagi uses sensors, LEDs and digital accounting. Materials and methods. The following processes form a research methodology called research and development, which include: potential and problems; data collection; product design; design validation; design revision; product trials; product revision; and mass production. Results. Based on research, 93% of Taekwondo I experts are good at stage I, and 95% are very good at stage II. The assessment for stage I was 75% good, while stage II was 95% very good, according to Taekwondo II experts. Electrical expert I gave a good rating of 74% for stage I and a very good score of 95% for stage II. The Phase I assessment for Electrical Expert II was 90% very good, and the Phase II assessment was 95% very good. Conclusions. In small group testing, 71% of trainer evaluation methods were considered very good; large group testing was 89.37%; and product testing was 89.37%.